Phenyl Extended Naphthalene‐Based Covalent Triazine Frameworks as Versatile Metal‐Free Heterogeneous Photocatalysts. Issue 2 (19th December 2021) - Fuerte-Díez, Beatriz; Valverde-González, Antonio; Pintado-Sierra, Mercedes; Díaz, Urbano; Sánchez, Félix; Maya, Eva M.; Iglesias, Marta
Abstract : Two new covalent triazines frameworks (CTFs) containing phenyl extended naphthalene units (with and without methoxy groups in the naphthalene core) are prepared by thermal and microwave activation. Both procedures yield similar chemical structures combining triazine acceptor units with donor aromatic groups, but they generate some differences in the morphology, structural organization, CO2 adsorption capacity, and thermal and optical properties. Besides, the methoxy groups of the naphthalene core have also influence in some of these properties. The resulting phenyl extended naphthalene CTFs are efficiently utilized as metal‐free heterogeneous photocatalyst for the selective aerobic oxidation of sulfides and the dehydrogenative cross‐coupling reactions under visible‐light irradiation, showing a high chemical stability. Abstract : Phenyl extended naphthalene‐based‐covalent triazine frameworks (PhN‐CTFs) result in effective heterogeneous photocatalysts for the metal‐free selective aerobic oxidation of sulfides to sulfoxides and the cross‐dehydrogenative C—C coupling reaction under visible‐blue light irradiation. The PhN‐CTFs also exhibited good substrates applicability for both reactions as well as excellent chemical stability.